Perancangan Website dan Penerapan Digital Marketing untuk UMKM Bahari Samudra dalam Meningkatkan Penjualan - Wahyu Kurnia Dewanto, S.Kom, MT; Muhammad Hafidh Firmansyah; Mochammad Rifki Ulil Albaab; Dhony Manggala Putra; Prisilia Angel Tantri (P3M Politeknik Negeri Jember, 2025)
Bahari Samudra MSMEs is a business engaged in marine aquaculture and fisheries, located in Banyuwangi, with lobsters and other marine fish as its main commodities. Despite having good cash flow, this MSME faces challenges in increasing sales because it still relies on traditional methods and lacks the use of digital technology. The main issues include the absence of a website, low knowledge of digital marketing, the lack of a digital financial recording system, and unstructured business management. This community service activity aims to improve the digital capacity of MSMEs through the following solutions: (1) website design and development, (2) digital marketing training, (3) digital accounting training, and (4) business management assistance. The implementation methods include preparation and field surveys, development of learning media, website implementation, training on the use of social media for marketing, and evaluation and monitoring. The expected outcomes of this activity are increased visibility and competitiveness of MSMEs, improved digital literacy, expanded market access, increased sales turnover, and contributions to strengthening the local economy. This program is designed as a concrete effort to encourage Bahari Samudra MSMEs to adapt to technological developments and changes in consumer behavior in the digital era.